Praca jako obowiązek a praca jako źródło satysfakcji. Studium historyczne roli i znaczenia pracy w dziejach Polski (po 1945 roku) - Kamosiński, Sławomir (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper presents an analysis of the ethical, political and economic aspects of human work within two Polish historical periods – the years of the People’s Republic of Poland and after 1989. The starting point for the analysis was the assumption that every time period, each age, leaves a mark on man’s work. Analysis of the People's Republic of Poland period gives an opportunity to consider human work understood as a duty and right of every human guaranteed by the Constitution of 1952. Questioning the principles ruling the labour market by the ideologists of the People’s Republic of Poland and, as a consequence, the politicization of labour, resulted in the collapse of the work ethic. Work, as it was at that time a commonly available good, lost its value, regarded as the source of life satisfaction, and thus became ridiculed. After 1989, in relation to the de-politicization of the Polish labour market, the employee became active in searching for a job. The phenomenon of unemployment resulted in competition on the labour market and the employer was thus given the opportunity to freely select a group of employees. As a result, the employer became a distributor of a ‘rare commodity.’ That, in turn, led to the situation where the approach of employers towards employees turned into the employer's diktat. It is the employer who determines the conditions of employment, standards of work and place of work. A lack of alternative that many employees face often makes them accept the dictated conditions of work. What is more, in Poland we deal with the insufficiently developed participation of employees in managing the enterprises, which is an effect of breaking off the bilateral dependency of employee and employer.